Health Services Use and Costs in Individuals with Autism Spectrum Disorder in Germany: Results from a Survey in ASD Outpatient Clinics. (1st June 2022) - Höfer, J.; Hoffmann, F.; Dörks, M.; Kamp-Becker, I.; Küpper, C.; Poustka, L.; Roepke, S.; Roessner, V.; Stroth, S.; Wolff, N.; Bachmann, C.
Abstract : Introduction: Autism spectrum disorders (ASD) are associated with high services use, but European data on costs are scarce. Objectives: Utilisation and annual costs of 385 individuals with ASD (aged 4-67 years; 18.2% females; 37.4% IQ < 85) from German outpatient clinics were assessed. Methods: Client Service Receipt Inventory Results: Average annual costs per person were 3287 EUR, with psychiatric inpatient care (19.8%), pharmacotherapy (11.1%), and occupational therapy (11.1%) being the largest cost components. Females incurred higher costs than males (4864 EUR vs. 2936 EUR). In a regression model, female sex (Cost Ratio: 1.65), lower IQ (1.90), and Asperger syndrome (1.54) were associated with higher costs. Conclusions: In conclusion, ASD-related health costs are comparable to those of schizophrenia, thus underlining its public health relevance. Higher costs in females demand further research. Disclosure: No significant relationships.